A QoE-driven traffic steering algorithm for LTE Networks - Marí-Altozano, María Luisa; Luna-Ramírez, Salvador; Gijón-Martín, Carolina; Toril-Genovés, Matías (My University, 2019)
Due to the huge increase in traffic and services in mobile networks, network management has changed its main focus from Quality of Service (QoS) to a Quality of Experience (QoE) perspective. In addition, SON (Self Organizing Networks) techniques have been developed to automate network management, being load balancing a key use case. Load balancing aim is to balance the traffic among adjacent cells. This balance is expected to decrease the overall blocking ratio, thus increasing the total carried traffic in the network. Nevertheless, these techniques may fail when QoE perspective is considered. In this work, a novel QoE balancing algorithm is proposed to reach QoE equilibrium in a realistic LTE network with different services. The proposed balancing approach is tested and compared with classical techniques by means of simulations.
Keywords: Ingeniería; QoE-driven; Traffic steering; LTE